The Dead Amongst the Living: Agency, Intention, and Power - Koski, Kaarina (Estonian Literary Museum, 2026)
The dead are viewed as having agency in this world when they make a difference to
our lives. This article explores the various forms of agency that the dead are felt to have. Also, it
looks at the power relations between the living and the dead. The research is based on archived
narratives and internet discussions produced in Finland in the 21st century. The dead can be felt
to have intentional agency that either derives from the past when they were alive, or emerges
from a spiritual realm. But usually, their agency is viewed as non-intentional. As such, it is only
represented by their memory or material objects in relation to the living in actor-networks. The
representations can also serve the intentions of the bereaved. After all, it is the living who narrate
the story of the dead, selecting what to include in it. Thus, there are even stories about deceased
people and haunting that are next to fiction. But in everyday life, close relatives may have had such
a formative role in one’s identity that one cannot control their, or even one’s own, story. The dead
can have agency without intentions.